Governing urban accessibility: moving beyond transport and mobility. Issue 1 (2nd January 2018) - Rode, Philipp; da Cruz, Nuno F.
Abstract: Access to people, goods, ideas and services is the basis of economic development in cities. The better this access, the greater the economic benefits through economies of scale, agglomeration effects and networking advantages. The way in which cities facilitate accessibility also impacts directly on other key aspects of human development, social inclusion and well-being. Accessibility is created through a complex interplay of urban form and transport systems. Thus, governing urban accessibility requires moving beyond conventional urban transport considerations linked to mobility and movement. Such a re-framing implies a far greater recognition of urban form characteristics like land use, distribution of densities and urban design, in addition to transport characteristics like infrastructures, service levels and travel speeds. A new interface between these characteristics has emerged as a result of shared mobility systems, putting additional pressure on city governments to act as system integrators. Based on a literature review, empirical insights from a global survey and the case-study cities of London, NYC and Berlin, this paper explores the institutional capacities of shifting from governing urban transport to urban accessibility. The evidence shows that there are entrenched misalignments which may impact negatively on the capacity to pair planning and policies essential for delivering better accessibility. Furthermore, it is clear that "hierarchies" and "networks" are not mutually exclusive when it comes to integrated governance of accessibility. The findings also suggest that cities may be better equipped to integrate shared mobility and consider mobility as a service than to pursue more wide-ranging metropolitan accessibility policies.